Peran Humas Pendidikan Anak Usia Dini Islam (THUFULA, 2020)
The objectives of this study are (1) to determine the role of PR (Public Relations) of PAUD Islam in the former area of Pati (2) to determine the implementation of Public Relations of Islamic PAUD in the area of the former Residency of Pati (3) to determine the obstacles in carrying out the role of PR of PAUD Islam in the former Karisidenan Pati. The type of research used is qualitative with a field research approach. Methods of data collection using interviews, observation and documentation. Data validity using data triangulation. The results showed (1) Public relations played an important role in the progress of Islamic PAUD in the former Pati Karisidenan area. The activities carried out were starting from the admission of new students, parenting. (2) Implementation of PR in the former Pati Karisidenan starts from planning, implementation and the last is evaluation. (3) Obstacles in implementing public relations include parents and the community who do not participate in public relations activities, to deal with this problem the school provides guidance to parents through parenting activities which are carried out regularly.